H. R. Polt, Jovellanos and his English sources. Economic, philosophical, and political writings. The American Philosophical Society, Philadelphia, 1964. (Transactions, New series, Vol. 54, Part 7). - Helman, Edith (El Colegio de México, 1966)
Se reseñó el libro: Jovellanos and his English sources. Economic, philosophical, and political writings.